FASAKH PERKAWINAN KARENA ALASAN CACAT BADAN MENURUT PANDANGAN WAHBAH AZ-ZUHAILI DAN IMAM MADZHAB - Icep Maulana Mansur Hidayat; Mustopa Kamal; Ahmad Nabil Atoillah (Istinbath | Jurnal Penelitian Hukum Islam, 2018)
Every household is not always peaceful, there are always problems that occur in it and often choose divorce as the final solution. One of the factors causing divorce is that one of the husband and wife finds a defect in their partner. Disability is one example of the reason why household life is no longer harmonious, because the interaction between husband and wife will be hampered, causing one party not to carry out their obligations. The principle of Islamic marriage law states that the marriage bond must not cause suffering to a partner or cause him to violate the boundaries set by Allah. If there is no option to terminate marriage for the aforementioned reasons to result in suffering to the normal partner, there is also the constant danger that hatred and sexual urges could cause the normal partner to violate God's provisions. These incidents resulted in the wife's complaint to the Religious Court to settle the case. In the Islamic view, divorce is not only the right of a husband but also the right of a wife, in this case it can be done by the wife by way of fasakh. The objectives of this study were: 1) To find out Wahbah Az-Zuhaili's views on the principles of marriage due to physical disabilities; 2) To find out Wahbah Az-Zuhaili's reasons regarding the fasakh of marriage due to physical disabilities; 3) To find out the views of Imam Madzhab on the principles of marriage for reasons of disability. This research uses qualitative research with content analysis method. While the data collection technique used is library research (library research). After the data has been collected, it is analyzed in stages: a) Data collection; b) Data reduction; c) Display data. This study resulted in the following conclusions: 1) Wahbah Az-Zuhaili allowed to sue fasakh due to a disability in one of the husband and wife. Separation must be made by the judge based on the complaint from the aggrieved party. For the defect which is used as the reason for this fasakh, Wahbah Az-Zuhaili has clearly specified and is very relevant to the advancement of the medical world; 2) The reason refers to the opinion of the four Imam Madzhab, Syi'ah Imamiyah, the Egyptian Law and the Syrian Law; 3) Two views of the Imam Madzhab regarding the principles of marriage for reasons of disability. First, the Zahiriyah Madzhab which states that they are defective cannot be used as an excuse for fasakh. Second, the view of the majority of Imam Madzhab that states that defects can be used as an excuse for fasakh, but they disagree over two things, namely about the right of who can sue fasakh and the details and limitations of defects that can be used as reasons for fasakh.